Implementation of the Sufficiency Economy Philosophy to the Pracharath Project Chiang Mai: Implementation of the Sufficiency Economy Philosophy to the Pracharath Project Chiang Mai - Chaiprasit, Khosit (Journal of Graduate MCU KhonKaen Campus, 2022)
The research purposes were 1) to study the context of the Pracharath project in Chiang Mai, 2) to study the philosophy of sufficiency economy concept to strengthen basic economics of the Pracharath Project and 3) to propose ways to implement the philosophy of sufficiency economy project to strengthen basic economics of Pracharath project guidelines. The study was a mixed method research. The sample group included 250 projects. The data were analyzed using rating scale, descriptive statistics, percentage, mean, and standard deviation. In-depth interview was also included for 3 successful projects. This research found that 1. Conducting business by applying the Sufficiency Economy Philosophy to strengthen the community economy at a moderate level ( =3.28). 2. The strength of the basic economy according to the Pracharat Project approach was at a high level ( = 3.51). 3. Applying the Sufficiency Economy Philosophy in each issue, namely moderation, rationality, and immunity make the community economy strong the community earns more. and the community is happy at a high level in all The research was also found that the achievement of the project was related to the social capital of the community including 1) community culture 2) humans 3) several organizations as well as different groups in the communities. 4) community networks and 5) local wisdom. These would increase community income, strengthen community economy, and build up the happiness to develop the quality of life of the people in the communities. These would also reduce both social and economic inequalities.